2018
DOI: 10.1186/s41077-018-0062-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a full-time, immersive simulation-based clinical placement on physiotherapy student confidence during the transition to clinical practice

Abstract: BackgroundNovice students may have limited learning opportunities during their early exposure to complex clinical environments, due to the priorities of patient care. Immersive, high-fidelity simulation provides an opportunity for physiotherapy students to be exposed to relatively complex scenarios in a safe learning environment before transitioning to the clinical setting. The present study evaluated the influence of immersive simulation on student confidence and competence.MethodsSixty penultimate year physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
104
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(112 citation statements)
references
References 21 publications
7
104
0
1
Order By: Relevance
“…While the improvements to self-efficacy observed in this study are significant, these improvements to significant improvements in student performance, (28,43) improved patient care and better patient outcomes, (49) strengthening the suggestion that these improvements to self-efficacy may translate to improved performance with real patients. However, students who receive SBE also may be more likely to overestimate their ability (50) and are likely to be less realistic in their selfevaluation in a simulated environment.…”
Section: Translation To Performancesupporting
confidence: 53%
“…While the improvements to self-efficacy observed in this study are significant, these improvements to significant improvements in student performance, (28,43) improved patient care and better patient outcomes, (49) strengthening the suggestion that these improvements to self-efficacy may translate to improved performance with real patients. However, students who receive SBE also may be more likely to overestimate their ability (50) and are likely to be less realistic in their selfevaluation in a simulated environment.…”
Section: Translation To Performancesupporting
confidence: 53%
“…Previous research has also shown students to have higher levels of confidence in their communication skills compared to their confidence in treatment and hazard awareness. (43) It is likely that students were more confident with their communication and interpersonal skills prior to SBE as they have had the more opportunities to develop these skills throughout the early years of their program of study.…”
Section: Discussionmentioning
confidence: 99%
“…While the improvements to self-efficacy observed in this study are significant, these improvements may not translate to an improved level of workplace-based clinical performance. The self-efficacy questionnaires provide a measure of perceived confidence in students' knowledge, skills and attitudes, demonstrating that they have achieved a degree of learning, according to the Kirkpatrick- to significant improvements in student performance, (28,43) improved patient care and better patient outcomes, (49) strengthening the suggestion that these improvements to self-efficacy may translate to improved performance with real patients. However, students who receive SBE also may be more likely to overestimate their ability (50) and are likely to be less realistic in their selfevaluation in a simulated environment.…”
Section: Translation To Performancementioning
confidence: 99%